A study on challenges in assessing free cataract surgery services in India: a gender perspective - Vishwakarma, Pankaj; Mondal, Amit; Ranpise, Dhanaji; Sundararaj, Lijiraj; Shaikh, Shajer; Chavan, Shobhana; Kurian, Elizabeth (International Journal Of Community Medicine And Public Health, 2025)
Background: Cataracts are the leading cause of blindness worldwide, accounting for 51% of cases as per World Health Organization (WHO). Despite cataract surgery being cost-effective, accessibility remains a challenge, particularly in low-income settings. Barriers include affordability, geographic constraints, and cultural acceptability. Gender disparities further limit access, as women—who form a larger proportion of visually impaired individuals—are less likely to receive surgery due to social and economic factors. This study examines cataract surgery accessibility through a gender perspective, identifying systemic, financial, and cultural barriers. Methods: A multicentre, retrospective study was conducted across 15 diverse locations in India, covering urban, semi-urban, and rural regions. Patient records of individuals who underwent free cataract surgeries were analyzed. Data were collected via structured telephonic interviews, including demographics, socioeconomic status, and perceived barriers. A total of 1,361 patients participated (53% female, 47% male). Statistical analyses, including Chi-square tests, assessed gender-based disparities. Results: Most respondents (60.18%) independently attended eye screening camps, with males (73.57%) being more self-driven than females (48.04%). Family, especially sons and spouses, influenced women’s decisions. Mobility challenges, financial dependency, and sociocultural norms limited women’s access. While 76.05% were confident about future hospital visits, 14.62% cited transport, financial, or health concerns. Conclusions: Gender-based barriers in cataract surgery access must be addressed through community outreach, financial support, and culturally sensitive education campaigns. Targeted interventions are essential to ensuring equitable eye care, reducing preventable blindness, and improving women’s healthcare access and participation. Future research should focus on region-specific policies promoting gender-inclusive eye care.